Modification of Silica Xerogels with Polydopamine for Lipase B from Candida antarctica Immobilization - Honghai Wang; Wenda Yue; Shuling Zhang; Yu Zhang; Chunli Li; Weiyi Su (Catalysts, 2021)
Silica xerogels have been proposed as a potential support to immobilize enzymes. Improving xerogels’ interactions with such enzymes and their mechanical strengths is critical to their practical applications. Herein, based on the mussel-inspired chemistry, we demonstrated a simple and highly effective strategy for stabilizing enzymes embedded inside silica xerogels by a polydopamine (PDA) coating through in-situ polymerization. The modified silica xerogels were characterized by scanning and transmission electron microscopy, Fourier tranform infrared spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy and pore structure analyses. When the PDA-modified silica xerogels were used to immobilize enzymes of Candida antarctica lipase B (CALB), they exhibited a high loading ability of 45.6 mg/gsupport, which was higher than that of immobilized CALB in silica xerogels (28.5 mg/gsupport). The immobilized CALB of the PDA-modified silica xerogels retained 71.4% of their initial activities after 90 days of storage, whereas the free CALB retained only 30.2%. Moreover, compared with the immobilization of enzymes in silica xerogels, the mechanical properties, thermal stability and reusability of enzymes immobilized in PDA-modified silica xerogels were also improved significantly. These advantages indicate that the new hybrid material can be used as a low-cost and effective immobilized-enzyme support.